Diet, lifestyle and chronic widespread pain: Results from the 1958 British Birth Cohort Study - VanDenKerkhof, Elizabeth G (Pulsus Group Inc, 2011)
OBJECTIVES: To examine the relationship between diet and lifestyle, and chronic widespread pain (CWP). If persons with CWP have dietary and lifestyle habits consistent with an increased risk of cancer or cardiovascular disease, it may partially explain evidence in the literature suggesting an association between CWP and these diseases. METHODS: The 1958 British Birth Cohort Study comprises individuals born in England, Scotland and Wales in the United Kingdom during one week in March 1958. At 45 years of age, pain was recorded using a self-completion questionnaire. CWP was classified using the American College of Rheumatology definition for fibromyalgia. Data were collected on diet and lifestyle at 33 and 42 years of age. RESULTS: A total of 8572 participants provided pain data at 45 years of age, of whom 12% reported CWP. Women with CWP, compared with those without, reported an unhealthy diet (ie, fruit/vegetable consumption less than once per week [OR 2.0; 95% CI 1.3 to 3.1], and fatty food [OR 1.7; 95% CI 1.1 to 2.7] and chips (french fries) [OR 1.5; 95% CI 1.0 to 2.4] at least once per day) that may have predisposed them to other chronic diseases such as cancer and cardiovascular disease. Women with CWP were also more likely to be unemployed (adjusted OR 1.4; 95% CI 1.1 to 1.8), to have had high physical exertion at work (adjusted OR 1.6; 95% CI 1.2 to 2.2) and elevated body mass index (overweight – adjusted OR 1.5, 95% CI 1.2 to 1.9; obese – adjusted OR 1.8, 95% CI 1.3 to 2.5). Similar relationships between lifestyle (but not diet) and the risk of CWP were identified in men. CONCLUSIONS: The findings for smoking, body mass index and (for women) diet offer support for the hypothesis that lifestyle factors may partially explain the association between CWP and cancer or cardiovascular disease. Prospective studies are necessary to confirm this relationship.